In the table below, you are given nine points in 3D space, and you are told that they lie on an elliptical cylinder whose axis intersects the plane at . Find a unit vector along the cylinder axis, and a unit vector along the major axis of the cross section of the cylinder , the semi-major axis length , the semi-minor axis length of the elliptical cylinder cross section, as well as and , and compute . As your answer, enter .
Note: The difference between this problem and the previous one (in which you are given only eight points) is that here the equation of the cylinder can be identified directly, without the need for iterations of a numerical method (such as the Newton-Raphson multivariate method).
1 | 1.260899462 | 24.35230705 | 1.546748822 |
2 | -4.843424289 | 6.255753394 | -1.788005646 |
3 | -1.866259211 | 1.399083562 | -7.792366969 |
4 | 4.337138292 | 20.46783278 | 5.86563437 |
5 | 8.299753336 | 18.22521393 | 0.834023076 |
6 | 6.26432148 | 16.81155064 | 7.83081978 |
7 | 7.310917527 | 14.9386501 | 8.611263334 |
8 | 6.735299382 | -2.364106077 | -4.140237122 |
9 | 14.5848197 | 14.83563445 | 4.45653806 |
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let r = ( x , y , z ) , then the equation of an elliptical cylinder is
( r − r 0 ) T Q ( r − r 0 ) = 1 , where r 0 is the position vector of any point on the axis, and Q can be factored as Q = R D R T , with D = diag { d 1 , d 2 , 0 } , so that the third column of the rotation matrix R is a unit vector along the axis of the cylinder. Expanding the equation of the cylinder, we get,
r T Q r − 2 r T Q r 0 + r 0 T Q r 0 − 1 = 0
Now, let h = − 2 Q r 0 , c = r 0 T Q r 0 − 1 , then for each point r i = ( x i , y i , z i ) , i = 1 , 2 , . . . , 9 , we have
Q 1 1 x i 2 + Q 2 2 y i 2 + Q 3 3 z i 2 + 2 Q 1 2 x i y i + 2 Q 1 3 x i z i + 2 Q 2 3 y i z i + h 1 x i + h 2 y i + h 3 z i + c = 0
This is a system of nine equations in ten unknowns, and can be solved using standard linear algebra methods, to yield:
Q = t Q 0 , h = t h 0 , c = t , t ∈ R
where
Q 0 = ⎣ ⎡ 0 . 0 2 9 1 4 3 3 7 5 0 . 0 1 5 7 5 5 3 7 7 − 0 . 0 3 7 2 3 1 2 4 4 0 . 0 1 5 7 5 5 3 7 7 0 . 0 1 6 8 8 6 5 2 2 − 0 . 0 1 1 1 5 4 2 1 5 − 0 . 0 3 7 2 3 1 2 4 4 − 0 . 0 1 1 1 5 4 2 1 5 0 . 0 5 7 1 8 5 6 2 7 ⎦ ⎤
h 0 = ⎣ ⎡ − 0 . 5 4 8 2 5 4 5 3 5 − 0 . 4 6 3 7 7 3 4 5 3 0 . 5 2 0 9 3 4 2 4 7 ⎦ ⎤
Now since h = − 2 Q r 0 , then h 0 = − 2 Q 0 r 0 , and this system can be solved for r 0 , and there are infinite solution as one would expect because r 0 can be any point on the axis of the cylinder. Solving this 3 × 3 system of equations yields:
r 0 = ( 4 , 1 0 , 0 ) + s ( 1 . 8 5 7 1 9 7 4 7 2 , − 1 . 0 7 2 2 5 3 4 6 , 1 ) , s ∈ R . Taking s = 0 , then x 0 = 4 , y 0 = 1 0 are the coordinates of the point of intersection of the axis with the x y plane, and r 0 = ( 4 , 1 0 , 0 )
Next, diagonalize Q 0 = R D 0 R T , you get,
D 0 = diag { 0 . 0 1 5 5 8 2 8 2 2 , 0 . 0 8 7 6 3 2 7 0 1 , 0 }
with a corresponding R = ⎣ ⎡ 0 . 2 5 0 0 1 3 6 2 7 0 . 8 5 5 6 5 4 5 6 5 0 . 4 5 3 1 5 3 8 9 4 0 . 5 6 6 9 6 3 6 9 6 0 . 2 5 0 0 1 3 6 2 7 − 0 . 7 8 4 8 8 5 5 6 7 0 . 7 8 4 8 8 5 5 6 7 − 0 . 4 5 3 1 5 3 8 9 4 0 . 4 2 2 6 1 8 2 6 2 ⎦ ⎤
Since c = t = r 0 T Q r 0 − 1 = r 0 T ( t Q 0 ) r 0 − 1 , then t = r 0 T Q 0 r 0 − 1 1 = 0 . 4 1 4 0 1 4 1 5 8 2 4 3 5 7 6
Therefore, the diagonal matrix D = t D 0 = diag { 0 . 0 0 6 4 5 1 5 0 9 , 0 . 0 3 6 2 8 1 1 7 9 , 0 }
The semi-major axis length = a = 0 . 0 0 6 4 5 1 5 0 9 1 = 1 2 . 4 5
And the semi-minor axis length = b = 0 . 0 3 6 2 8 1 1 7 9 1 = 5 . 2 5
The vector u = ( 0 . 7 8 4 8 8 5 5 6 7 , − 0 . 4 5 3 1 5 3 8 9 4 , 0 . 4 2 2 6 1 8 2 6 2 ) is the unit vector along the axis of the cylinder, and
The vector v = ( 0 . 2 5 0 0 1 3 6 2 7 , 0 . 8 5 5 6 5 4 5 6 5 , 0 . 4 5 3 1 5 3 8 9 4 ) is the unit vector along the major axis of the elliptical cylinder's cross section.
Hence, S = 4 + 1 0 + 1 2 . 4 5 + 5 . 2 5 + 0 . 7 8 4 8 8 5 5 6 7 + 0 . 4 5 3 1 5 3 8 9 4 + 0 . 4 2 2 6 1 8 2 6 2 + 0 . 2 5 0 0 1 3 6 2 7 + 0 . 8 5 5 6 5 4 5 6 5 + 0 . 4 5 3 1 5 3 8 9 4 = 3 4 . 9 1 9 4 7 9 8 1 , so that the answer is ⌊ 3 4 . 9 1 9 4 7 9 8 1 × 1 0 5 ⌋ = 3 4 9 1 9 4 7